A Comprehensive Review: Synthesis and Pharmacological Activities of 1,3,4-Oxadiazole Hybrid Scaffolds - Lata, Suman; Choudhary, Lucky; Bharwal, Ankita; Pandit, Amit; Abbot, Vikrant (Medicinal Chemistry, 2025)
IntroductionHeterocyclic derivatives, particularly those containing heteroatoms such as oxygen and nitrogen, represent a significant portion of currently marketed drugs. Among these, the aromatic heterocycle 1,3,4-oxadiazole, characterized by an N=C=O-linkage, stands out due to its remarkable biological activities. These activities include anti-inflammatory, anti-cancer, antioxidant, anti-tubercular, antiviral, anti-diabetic, and antibacterial effects. Notably, several commercially available medications, such as tiodazosin, raltegravir, zibotentan, and nesapidil, incorporate this structural motif.MethodsThis review compiles and analyzes existing synthetic methods for preparing 1,3,4-oxadiazole and its derivatives. By examining various synthetic routes and methodologies, the review provides a detailed overview of the strategies employed to generate these biologically active compounds.ResultsThe review highlights the potential of 1,3,4-oxadiazole derivatives in addressing the toxicity, side effects, and drug resistance commonly associated with existing anticancer therapies. By combining the 1,3,4-oxadiazole moiety with other heteroatoms, novel hybrid derivatives have been synthesized, demonstrating enhanced pharmacological activities across various therapeutic areas.ConclusionThis comprehensive review offers valuable insights into the synthesis and pharmacological applications of 1,3,4-oxadiazoles. It serves as a crucial resource for researchers exploring the development of new therapeutic compounds, with the ultimate goal of improving public health. The review builds on existing literature from the last two decades to present an exhaustive examination of the potential of 1,3,4-oxadiazole derivatives in drug development.
Keywords: marketed drugs